Antibacterial Photodynamic Effect of 532 nm Diode-Pumped Solid State and 650 nm Diode Lasers on Methicillin Resistant Staphylococcus Aureus in Vitro - Abdulameer, Fadhaa H.; Maki, Amel M. (Iraqi Journal of Laser, 2019)
The photodynamic inactivation against Methicillin-resistant Staphylococcus aureus using two different lasers, 532 nm diode pumped solid state laser (DPSS) in combination with safranin O and 650 nm diode laser in combination with methylene blue was investigated in the present work. A hundred swab samples were collected from patients with burn and wound infections admitted to two hospitals in Baghdad (Specialized Burns Hospital in Medical City and Al Imamein Al Jwadein Medical City Hospital) from December 2015 to February 2016 Antimicrobial susceptibility was performed by using Kirby- Bauer method. The irradiation experiments included four groups; a control group, a photosensitizer only group, a laser irradiation only group and a laser irradiation combined with a photosensitizer group. The results showed that 532nm DPSS laser with power density 0.157 W/cm2 combined with 0.5 mg/ml safranin O was more effective than 650 nm diode laser with power density 0.052 W/cm2 combined with 0.1 mg/ml methylene blue in reducing the number of MRSA cells. One hundred percent killing of MRSA was achieved after 3 minutes exposure to 532 nm DPSS laser in combination with safranin O, while it took 11 minutes to achieve the same result using 650 nm diode laser and methylene blue. In conclusion, photodynamic inactivation can be considered as an alternative method in treating superficial burn wound infections